1975
DOI: 10.1083/jcb.64.2.398
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface changes and Rous sarcoma virus gene expression in synchronized cells.

Abstract: We have investigated whether cell surface changes associated with growth control and malignant transformation are linked to the cell cycle. Chicken embryo cells synchronized by double thymidine block were examined for cell-cycle-dependent alterations in membrane function (measured by transport of 2-deoxyglucose, uridine, thymidine, and mannitol), in cell surface morphology (examined by scanning electron microscopy), and in the ability of tumor virus gene expression to induce a transformation-specific change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 24 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…This observation confirms the previous report (3) (9) of cells infected with wild-type RSV (Schmidt-Ruppin strain). Probably the differences in appearance of the structures seen in our electron micrographs and those of Hale et al result from the long fixation period used by them, which we have found leads to partially degraded preparations.…”
Section: Resultssupporting
confidence: 82%
“…This observation confirms the previous report (3) (9) of cells infected with wild-type RSV (Schmidt-Ruppin strain). Probably the differences in appearance of the structures seen in our electron micrographs and those of Hale et al result from the long fixation period used by them, which we have found leads to partially degraded preparations.…”
Section: Resultssupporting
confidence: 82%
“…The cells used for the studies were in the confluent phase, 3 days after saturation, and they were stable morphologically and biologically without significant cell migration. Cells in this phase were reported to be density-inhibited and synchronized (5). The detailed methods for the light and electron microscopic studies have been described previously (6,7).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the surface of some monolayer cells undergoes distinct changes during the cell cycle (Rubin and Everhart, 1973;Porter et al, 1973;Hale et al, 1975). Cell-cycle related morphological changes have been described in feline lymphoid cells (Toth, 1981).…”
Section: Introductionmentioning
confidence: 99%